Getting Profitable CCU off the Ground: Contingent Pathways and Bergen Carbon Solutions - Sareen, Siddharth; Sagmo, Jan (Frontiers in Energy Research, 2021)
As Carbon Capture Utilisation and Storage (CCUS) gains policy traction and pilot project funding, CCS usually gets the limelight, whereas CCU is often overlooked. CCU, if feasible, has two potential advantages: it obviates risks and monitoring needs associated with long-term storage, and it creates economic value to offset carbon capture costs. Yet scholarly accounts of CCU feasibility are rare. To address this lacuna, the manuscript channels in-depth knowledge of a CCU start-up in Norway into a critical analysis of the barriers and opportunities for emerging sectoral enterprises. The trajectory of Bergen Carbon Solutions during 2016-2019 is mapped by a human geographer along with its founder. We organise enquiry along three axes: (i) access to ‘soft’ capital – this includes knowledge and human resources, (ii) access to ‘hard’ capital – this includes financing and technical approvals, and (iii) navigation of rapid expansion. Under (i), we present and analyse the contextual conditions and contingencies for the emergence of the core value proposition. Under (ii), we detail the networks, processes and institutional structures through which the enterprise gained its financial basis and was able to test its CCU process. Under (iii), we complement attention to organisational management by highlighting key informal and human factors. We foreground how the emergence of CCU is a relational process that depends on how actors in a changing field interact and reconfigure themselves. This informs regulatory policies and economic instruments about overlooked contextual issues related to the modulation and feasibility of scalable, profitable CCU.